DIVERSITY OF BIRDS ACROSS LAND USE AND HABITAT GRADIENTS IN FORESTS, RUBBER AGROFORESTS AND RUBBER PLANTATIONS OF NORTH SUMATRA - Ayat, Asep; Tata, Hesti L. (Indonesian Journal of Forestry Research, 2015)
Birds play a pivotal role in ecosystems, but in disturbed areas their role may be limited due to changes in their habitat. In Simalungun and Asahan districts, North Sumatra, bird communities were studied in a range of habitats: natural forest, rubber agroforests (RAF), rubber monoculture plantations (RMP) and emplacement areas. The birds were observed using descriptive survey methods by implementing a quick biodiversity survey, with data collected along a 1km transect. In total, 142 species of birds from 42 families were found in the four habitats. Natural forests held the highest diversity of bird species, followed by rubber agroforests, emplacement areas and rubber plantations, with a Shannon-Wiener index of 4.5, 3.6, 3.6 and 3, respectively. Regarding the IUCN red list species, 12 bird species of near-threatened status and 2 species of vulnerable status were recorded. Based on CITES categories, one species was listed in the Appendix criteria I, 12 species were classified in Appendix II and 26 bird species were protected under Indonesian regulations. Changes in the structure and composition of vegetation in disturbed forests and cleared land determined the richness of bird species. The different tree compositions in the three habitats of the rubber estate plantations and surrounding areas influenced the number of bird species, their diversity and species composition.